2023
DOI: 10.1002/aesr.202200141
|View full text |Cite
|
Sign up to set email alerts
|

Increased Photoelectrochemical Performance of Vanadium Oxide Thin Film by Helium Plasma Treatment with Auxiliary Molybdenum Deposition

Abstract: Helium (He) plasma treatment can be a versatile tool to fabricate nanostructures on a surface and change the surface chemistry. Herein, vanadium (V) thin film is exposed to helium plasmas and the changes in morphology and surface properties are investigated. The irradiation condition at which the surface morphology can be changed is identified. During the He plasma irradiation, molybdenum (Mo) from the sample cover deposits and formation of composite nanostructured photoelectrode with a combination of normalV2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…The high-resolution V2p spectra of the S3 sample (Figure 4b) indicate the presence of V ions in two different oxidation states, with peaks at binding energies of 523.24 eV and 516.15 eV corresponding to V 4+ and peaks at binding energies of 524.56 eV and 517.54 eV corresponding to V 5+ , a result that is in good agreement with the chemical state of vanadium in V 6 O 13 reported in the literature [31,40,41]. O1s high resolution spectrum (Figure 4b) shows the presence of vacant oxygen in sample S3, with peaks at binding energies of 529.82 eV corresponding to lattice oxygen (O latt ) and 530.69 eV corresponding to vacant oxygen (O d ) [34]. The high resolution spectra of S1, S2, S3, S4, and S5 V2p spectra (Figure 4c) and O1s spectra (Figure 4d) indicate the presence of V 4+ and V 5+ as well as oxygen vacancies at similar and variable levels in all samples.…”
Section: Characterizations Of Materialssupporting
confidence: 90%
See 1 more Smart Citation
“…The high-resolution V2p spectra of the S3 sample (Figure 4b) indicate the presence of V ions in two different oxidation states, with peaks at binding energies of 523.24 eV and 516.15 eV corresponding to V 4+ and peaks at binding energies of 524.56 eV and 517.54 eV corresponding to V 5+ , a result that is in good agreement with the chemical state of vanadium in V 6 O 13 reported in the literature [31,40,41]. O1s high resolution spectrum (Figure 4b) shows the presence of vacant oxygen in sample S3, with peaks at binding energies of 529.82 eV corresponding to lattice oxygen (O latt ) and 530.69 eV corresponding to vacant oxygen (O d ) [34]. The high resolution spectra of S1, S2, S3, S4, and S5 V2p spectra (Figure 4c) and O1s spectra (Figure 4d) indicate the presence of V 4+ and V 5+ as well as oxygen vacancies at similar and variable levels in all samples.…”
Section: Characterizations Of Materialssupporting
confidence: 90%
“…Researchers have utilized different methods to create oxygen vacancy defects in vanadium oxides. For example, vanadium oxides with abundant oxygen vacancy defects have been prepared by means of elemental doping [31], water vapor activation [32], the electron beam evaporation method [33], exposure to plasma [34], etc. Therefore, V 6 O 13 powders rich in oxygen vacancy defects are worth exploring in depth in terms of anti-Candida albicans.…”
Section: Introductionmentioning
confidence: 99%
“…TMOs with oxygen vacancies are considered prospective materials to increase the catalytic activity of a catalyst, 16 and help to tune the bandgap and provide more active sites and have favorable Gibbs hydrogen adsorption free energies. 17 Formation of heterostructures is another means to decrease the charge recombination and increase the photocatalytic efficiency. 16 Formation of a heterostructure of TMO and TMC with appropriate band gap alignment is a potential method to improve the HER, which is addressed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Applications using fuzzy metals have been explored, especially after oxidation, for light absorbers, 16) light diffusers, 17) gas sensors, 18,19) photocatalysts, [20][21][22][23] and photoelectrochemical oxygen evolution reactions (OERs). [24][25][26][27][28] In addition to metals, the effects of He plasma irradiation on several semiconductors, including silicon (Si) and germanium (Ge), which have rather low bandgap energies, have been investigated. It was found that He plasma irradiation leads to the formation of black Si with nanocones on the surface.…”
Section: Introductionmentioning
confidence: 99%